2009
DOI: 10.1159/000243164
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of the Characteristics of Reported Elder Self-Neglect in a Community-Dwelling Population: Findings from a Population-Based Cohort

Abstract: Background: Elder self-neglect is an important public health issue. However, little is known about the characteristics of self-neglect and its association with social factors among community-dwelling populations. Objectives: (1) To examine the sociodemographic, health-related and psychosocial characteristics of reported elder self-neglect; (2) to examine the association of social network and social engagement with reported self-neglect. Methods: Population-based study conducted from 1993 to 2005 of community-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 46 publications
2
53
1
Order By: Relevance
“…Thus, current knowledge of the association of elder self-neglect with psychological, health, and social factors in the general population is highly limited. In addition, prior studies suggest that black older adults are more frequently reported to social services agency for elder self-neglect (Dong, Simon, & Evans, 2009b). However, we are not aware of any studies that have examined the black and white differences in these associations in a racially/ethnically diverse population.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, current knowledge of the association of elder self-neglect with psychological, health, and social factors in the general population is highly limited. In addition, prior studies suggest that black older adults are more frequently reported to social services agency for elder self-neglect (Dong, Simon, & Evans, 2009b). However, we are not aware of any studies that have examined the black and white differences in these associations in a racially/ethnically diverse population.…”
Section: Introductionmentioning
confidence: 87%
“…Severity of self neglect is scored along this continuum using a 0-45 scale, based on the concerns for personal health and safety issues. Details of the self-neglect severity scale have been published previously (Dong et al, 2009a;2009b;Dong, Mendes de Leon, & Evans, 2009c). In brief, the self-neglect severity was measured based on the degree of unmet…”
Section: Assessment Of Self-neglect Severitymentioning
confidence: 99%
“…Studies reveal that abuse may cause mental disorders such as depression and anxiety, and decreases the life quality of the elderly (8,13,14). Dong`s studies in Chicago showed that the elderly who encountered abuse had higher level of depression in comparison with the others (13,15). According to the National Center on Elder Abuse of the USA, out of 10 American elderly, one experiences abuse, annually; while just one out of 14 is reported (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences influence elder abuse according to different reports (10). Age, sex, unemployment, insurance situation, education, level of depression, chronic disease and disabilities are among the factors associated with abuse (2,15,23,27). Considering the impact of culture on elder abuse, diversity of the Iranian culture and national healthcare system, the important role of this subject on health promotion and improving quality of life in elderly and insufficient information in this issue motivated the researchers to design and conduct a study to determine the level of abuse and its associated factors among the elderly of Kashan city, Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, social services agency data suggest that minority older adults and those with lower levels of socioeconomic status may be at higher risk of being reported to authorities for these behaviors [4,9,10] . However, there remain significant gaps in our current understanding of the scope of these issues in representative populations.…”
Section: Introductionmentioning
confidence: 99%